Co-creating experiences through the use of arts in social work education - Tracey Maegusuku-Hewett (Social Work Education, 2024)
The inclusion of citizens in social work education was initiated over 30 years ago and continues to travel a ‘long and winding road’. Social work education in the UK faces increasing pressure from a range of stakeholders including citizens who use services, regulatory bodies and the media to demonstrate that newly qualified social workers are competent and uphold public trust. While social work education and practice within England and Wales draw on similar traditions in theory and practice, there are important differences in the national and institutional frameworks within which they operate. This article illustrates some of these differences through a focus on social work education provision in one English and one Welsh university. Drawing on the experience and views of the student participants, we examine the benefits of creative approaches that promote citizen involvement and suggest how European traditions can contribute to this process. We define key terms and summarize the literature, followed by presentation of the results and identification of the key learning. We identify that emancipatory models of education can encourage recognition of learners’ different strengths and can help to assist social work students’ readiness for practice. Finally, we acknowledge the need for cost-benefit outcomes research into if and how citizen coproduction influences subsequent service delivery.